The Influence of Microstructure on Nanomechanical and Diffusion Barrier Properties of Thin PECVD SiOx Films Deposited on Parylene C Substrates - Framil, David; Van Gompel, Matthias; Bourgeois, Florian; Furno, Ivo; Leterrier, Yves (Frontiers in Materials, 2019)
Plasma-enhanced chemical vapor deposition (PECVD) was used to deposit SiOx thin films of varying thicknesses on parylene C substrates, using hexamethyldisiloxane (HMDSO) as a precursor. The microstructure of SiOx coatings was analyzed using X-ray photoemission spectroscopy (XPS), nanoindentation, and spectroscopic ellipsometry. The composition ranged from oxygen-rich oxides with large silanol OH content to hybrid oxides with larger organic content, while refractive index varied from 1.45 to 1.5 depending on the specimen. Reduced moduli of coatings obtained by nanoindentation varied between 15 and 59 GPa and could be correlated with permeability to oxygen and water vapor through the existence of porosity in a broader sense. It can be concluded that the barrier properties are the result of a complex interplay of microstructural features, with porosity, silanol and carbon content playing important roles in the final thin film properties.